2018
DOI: 10.1002/adom.201801409
|View full text |Cite
|
Sign up to set email alerts
|

Supersmooth Ta2O5/Ag/Polyetherimide Film as the Rear Transparent Electrode for High Performance Semitransparent Perovskite Solar Cells

Abstract: Semitransparent solar cells have attractedincreasing attention because of their gen eral applications in smart windows for automobiles and buildings, tandem solar cells, electronic chargers, and so on. [1][2][3] Due to facile solution processing and high record efficiency of 23.3% in nontrans parent devices, [4][5][6][7][8] organic-inorganic lead halide perovskite solar cells (PSCs) are excellent candidates for semitransparent devices, since the efficiency of semi transparent devices is inevitably lower compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Ta 2 O 5 -ZnO composite film has been used as a cathodic buffer layer for inverted polymer solar cells to get enhanced efficiency [ 39 ]. In an interesting work by Ying et al, a combination of ZrAcac/PEI/Ag/Ta 2 O 5 was employed as the rear transparent electrode of semi-transparent PSCs, leading to enhanced transmittance [ 40 ]. It is suggested that materials with high dielectric constants could offer better charge separation and improve the photovoltaic efficiency by suppressing the carrier recombination across the interfaces [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ta 2 O 5 -ZnO composite film has been used as a cathodic buffer layer for inverted polymer solar cells to get enhanced efficiency [ 39 ]. In an interesting work by Ying et al, a combination of ZrAcac/PEI/Ag/Ta 2 O 5 was employed as the rear transparent electrode of semi-transparent PSCs, leading to enhanced transmittance [ 40 ]. It is suggested that materials with high dielectric constants could offer better charge separation and improve the photovoltaic efficiency by suppressing the carrier recombination across the interfaces [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of PEI as wetting layer has been reported to induce smooth growth of Ag film. [47,49] While, the ZnO NP serves to facilitate charge collection. As shown in Figure 3c,d, the PEI modification induces smoother film, and significantly decreases the surface roughness from 3.13 to 1.67 nm, compared to that with PFN-Br.…”
Section: Transparent Electrode Optimizationmentioning
confidence: 99%
“…[19] A branched polyethylenimine (PEI) layer is deposited on top of ZnO nanoparticles (NP) layer to reduce the granule size of ultra-thin Ag transparent electrode. [47][48][49] The resultant smooth ultra-thin Ag film effectively alleviates light scattering and improves the absorbing selectivity of ST-OPV. Further, with the guidance of optical simulation, an optical interference layer, that is, TeO 2 , is deposited on top of the ultra-thin Ag layer, and this dramatically improves absorbing selectivity via increasing the transmittance in visible region without significantly sacrificing absorption in invisible region.…”
Section: Introductionmentioning
confidence: 99%
“…The DMD structures in ST‐PSCs have been similar to those in ST‐OPVs. [ 33,45,48,49,73,74,78,79,117–122 ] For example, Hanmandlu et al introduced a 2,9‐dimethyl‐4,7‐diphenyl‐1,10‐phenanthroline (BCP)/Ag/MoO 3 transparent electrode for bifacial PSCs (Figure 2d). [ 79 ] In addition to providing a high dielectric constant, the BCP also functioned as a diffusion buffer layer between the electron transport layer (ETL) and the Ag electrode.…”
Section: Semitransparent Opvs and Pscsmentioning
confidence: 99%